Intrauterine devices influence prostaglandin secretion by equine uterus: in vitro and in vivo studies - Katarzyna Karolina Piotrowska-Tomala; Agnieszka Walentyna Jonczyk; Anna Szóstek-Mioduchowska; Takuo Hojo; Ewelina Żebrowska; Terttu Katila; Graca Ferreira-Dias; Dariusz Jan Skarzynski (BMC Veterinary Research, 2024)
Abstract Background Intrauterine devices (IUD) are used in the veterinary practice as the non-pharmacological method of oestrus suppression in mares. When placed in the uterus, IUD create a physical contact with the endometrium that mimics the presence of an equine embryo. However, the mechanism of their action has not been fully elucidated. The objective of the present study was to examine the effect of mechanical stimulation of IUD on mare`s endometrium in both in vitro and in vivo study. For this purpose, we demonstrated the effect of IUD on prostaglandin (PG) F2α and PGE2 secretion, and mRNA transcription of genes involved in PG synthesis pathway in equine endometrial cells in vitro. In the in vivo study, we aimed to compare short-term effect of IUD inserted on day 0 (oestrus) with day 5–6 post-ovulation (the specific time when embryo reaches uterus after fertilization) on PG secretion from equine endometrium. To determine the long-term effect on PG synthase mRNA transcription, a single endometrial biopsy was taken only once within each group of mares at certain time points of the estrous cycle from mares placement with IUD on days 0 or 5–6 post-ovualtion. Results We showed for the first time that the incubation of the endometrial cells with the presence of IUD altered the pattern of PG synthase mRNA transcription in equine epithelial and stromal endometrial cells. In vivo, in mares placement with IUD on day 0, PGE2 concentrations in blood plasma were upregulated between 1 and 6, and at 10 h after the IUD insertion, compared with the control mares (P < 0.05). Moreover, the decrease of PTGFS mRNA transcription on day 16- 18, associated with an elevation in PTGES mRNA transcription on day 20 -21 of the estrous cycle in endometrial biopsies collected from mares placement with IUD on days 5–6 suggest an antiluteolytic action of IUD during the estrous cycle. Conclusion We conclude that the application of IUD may mimic the equine conceptus presence through the physical contact with the endometrium altering PG synthase transcription, and act as a potent modulator of endometrial PG secretion both in vitro and in vivo.